The languages of Malta - Paggio, Patrizia; Gatt, Albert (Studies in Diversity Linguistics, 2018)
The purpose of this volume is to present a snapshot of the state of the art of research on the languages of the Maltese islands, which include spoken Maltese, Maltese English and Maltese Sign Language.Malta is a tiny, but densely populated country, with over 422,000 inhabitants spread over only 316 square kilometers. It is a bilingual country, with Maltese and English enjoying the status of official languages. Maltese is a descendant of Arabic, but due to the history of the island, it has borrowed extensively from Sicilian, Italian and English. Furthermore, local dialects still coexist alongside the official standard language. The status of English as a second language dates back to British colonial rule, and just as in other former British colonies, a characteristic Maltese variety of English has developed. To these languages must be added Maltese Sign Language, which is the language of the Maltese Deaf community. This was recently recognised as Malta's third official language by an act of Parliament in 2016.